Eficiência de absorção de nitrogênio e dinâmica do crescimento do sistema radicular de Vitis vinifera e Eucalyptus sp. submetidos à adubação nitrogenada - Kulmann, Matheus Severo de Souza (2019)
Sandy soils and with low organic matter content do not provide provide enough nitrogen (N) to supply the demand of Vitis vinifera and Eucalyptus sp. However, the applied N is not always used in large quantities by these crops. Therefore, it is advisable to select the most efficient rootstocks and clones for N uptake. Also, define the best N doses and modes of supply that can promote adequate root system growth, favoring water and nutrient uptake, such as mineral forms of N, which may promote high yields, but as quality grapes; as well as rapid growth in the case of Eucalyptus sp. This will promote rationalization of fertilizers and decrease environmental contamination. The work aimed to establish the efficiency of N uptake and root growth dynamics in Vitis vinifera and Eucalyptus sp., submitted to nitrogen fertilization. Two studies were conducted. Each study consisted of two experiments, one with grapevine and one with eucalyptus. Study 1 included selecting of vines rootstocks and eucalyptus clones for the uptake efficiency of N. An experiment with two grapevine rootstocks (“Paulsen 1103” and “Magnólia”) and, another with two eucalyptus clones (“Eucalyptus saligna (32864)” and “Eucalyptus grandis (GPC 23)”), it was conducted. The vines rootstocks and eucalyptus clones were cultivated for 20 and 30 days, respectively, in pots containing solution with Ca- SO4 to 0,1 mol L-1. After, chlorophyll a fluorescence and photosynthetic rates were evaluated. The plants were again subjected to Hoagland solution, where periodic solution collections were performed during 65 hours of evaluation. After, shoot and root system morphological parameters, dry matter, N concentration were evaluated. The kinetic parameters of the uptake of NO3 - and NH4 +. (maximum absorption speed - Vmax, Michaelis-Menten constant - Km, minimum concentration - Cmin and influx - I)) were calculated using Influx software. Study 2 addressed the effect of N modes and doses on root system growth. In Experiment 1 'Alicante Bouschet' grapevines, grafted onto Paulsen 1103 rootstock were submitted to applications of 0, 40 and 100 kg kg N ha-1 year-1, supplied without irrigation (N surf) and via fertigation (N Fert). In the experiment 2 Eucalyptus grandis clones (GPC 23) were submitted to control (without N) (C), surface N (SN) and N in hole (CN). Leaf N concentration, yield components and root growth parameters (surface area, number, production and average diameter of roots) using minirhizotron were evaluated. In Study 1, Paulsen 1103 rootstock and Eucalyptus grandis clone presented higher NO3 - and NH4 + uptake efficiency, since they presented lower Cmin and Km values, in both forms of N, which allows the extraction of N by roots, even in low concentrations in solution due to the higher affinity of the root uptake sites for NO3 - and NH4 +.The parameters of root length, surface area aid the Paulsen 1103 rootstock and Eucalyptus grandis clone in their absorption efficiency and, consequently, better photosynthetic performance and higher root and shoot dry matter production. In Study 2 the highest doses of N (40 and 100 kg N ha-1 year-1) for grapevine and the CN mode for eucalyptus increased higher levels of NO3 - and NH4 + in the soil, which stimulated higher values of production and surface área of roots. This contributes to higher N uptake, as observed in leaf N concentration, which increased production parameters such as eucalyptus height and stem diameter, productivity and number of vine clusters. However, increased productivity altered grape must composition, especially increasing total titratable acidity and reducing total anthocyanin and total soluble solids contents.